2000
DOI: 10.1161/01.cir.102.7.766
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrasonic Tissue Characterization Can Identify High-Risk Atherosclerotic Alteration in Human Carotid Arteries

Abstract: Background-Recently, ultrasonic tissue characterization of the composition of plaques has been performed in a quantitative fashion on the basis of integrated backscatter (IBS) analysis, but most of those studies have used high-frequency ultrasound to obtain microscopic images. Methods and Results-We performed B-mode measurement and IBS signal analysis with acoustic densitometry with a 7.5-MHz linear-array transducer in freshly excised human aortas (nϭ58) (normal, atheromatous, and fibrous tissue) obtained at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 35 publications
4
105
0
1
Order By: Relevance
“…Advanced mathematical algorithms including radiofrequency analysis (RFA) and elastography allow a more detailed analysis 96,97 . IVUS-derived RFA (virtual histology, VH-IVUS) displays the reconstructed data as a color coded tissue map of plaque composition based on validation to histology [98][99][100] . VH-IVUS classifies plaque components into four basic tissue types: fibrous (dark-green), fibro-fatty (light-green), necrotic core (red), and dense calcium (white) 101 .…”
Section: Plaque Composition With Ivusmentioning
confidence: 99%
“…Advanced mathematical algorithms including radiofrequency analysis (RFA) and elastography allow a more detailed analysis 96,97 . IVUS-derived RFA (virtual histology, VH-IVUS) displays the reconstructed data as a color coded tissue map of plaque composition based on validation to histology [98][99][100] . VH-IVUS classifies plaque components into four basic tissue types: fibrous (dark-green), fibro-fatty (light-green), necrotic core (red), and dense calcium (white) 101 .…”
Section: Plaque Composition With Ivusmentioning
confidence: 99%
“…The system automatically calculated the average value of the IBS, which was also displayed in dB. By adopting the adventitia as the reference object, we then corrected the IBS value (C-IBS) by subtracting the IBS value obtained from a reference ROI placed within the adventitia (23,27).…”
Section: Integrated Backscatter Analysis (Ibs)mentioning
confidence: 99%
“…Thus, acoustic densitometry is now believed to be a clinically applicable ultrasonic backscatter imaging technology that provides an integrated online capability to measure, display and quantify the presence of fibrous tissue in intima-media complex of human arteries. This relatively simple, repeatable and quantitative analysis is able to evaluate the vascular structure in a non-invasive manner (23).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with acoustic densitometry, IBS offers a clinically promising method for assessing myocardial contractile performance independent of wall motion 37)38) or quantitative evaluation of the vessel wall plaque composition: fibrosis, calcification, or lipid deposition. 39)40) The latter approach can provide for a new evaluation of thoracic aortic atherosclerosis. Wickline et al 36) have shown that IBS can be applied to aortic atherosclerosis in vivo.…”
Section: Possible New Index Of Aortic Atherosclerosismentioning
confidence: 99%
“…However, IBS has not been established as a standard reference. The authors have used the IBS signal from the vessel lumen as a reference object, while other investigators have used left ventricular cavity, 41) myocardium, 42) pericardium, 43) and adventitia 39) as references. The established standard reference tissue for quantitative ultrasonic tissue characterization with IBS analysis is indispensable when this index is used as a 'noninvasive ultrasonic biopsy' in the clinical setting.…”
Section: Possible New Index Of Aortic Atherosclerosismentioning
confidence: 99%